Analisis Penilaian Beban Kerja Mental pada Pekerja Assembly di PT. XYZ dengan Menggunakan Metode NASA-TLX - Rea Afifah Prafitria Cahyanie; Dene Herwanto (Peneliti.net, 2022)
PT. XYZ is a manufacturing company that produces gaskets and rockwool in it. Departments at PT. XYZ is one of them is the assembly section, where the assembly is still done manually. Examples include hammering, cutting, and even pulling which can pose a work risk if done continuously. The work in this section is done sitting for 8 hours every day. Every day workers are required to be able to work to achieve the targets given by the company. Researchers used the NASA-TLX (National Aeronautics and Space Administration Task Load Index) method. This method is carried out by distributing questionnaires to workers to be able to find out the mental workload that workers feel while doing work. This method is based on six dimensions namely Mental, Physical, Time, Performance, Effort and Frustration. There were 5 respondents who were asked to fill out this questionnaire. The results of this study were 41% of workers with